Resiliency and dyeability of environmentally friendly polypropylene/poly (trimethylene terephthalate)/nanoclay blend nanocomposite fibers - Habibolah Zargar, Mohammad Reza; Ehsani, Morteza; Ebrahimzade, Amin; Nobre, Marcos A. L. [UNESP]; Mousavi Shoushtari, Seyed Ahmad; Khonakdar, Hossein Ali (Taylor & Francis, 2024)
An environmentally friendly free-carrier procedure was used to prepare polypropylene/poly(trimethylene terephthalate)/nanoclay (PP/PTT/NC) blend nanocomposite fibers. Adding NC to the PP/PTT blend diminished the average diameter of PTT from 140 mm for the PP/PTT blend to 85 mm for the blend containing 1 phr nanoclay. Moreover, adding PTT and NC did not affect the mechanical properties of PP significantly. The crystallinity of the PP blend increased by almost 15% when 10 wt.% PTT and 1 phr NC were added. Molten neat PP and its blends and blend nanocomposites showed a typical pseudo-plastic flow behavior. Also, the storage modulus of all samples increased nearly linearly in the frequency range of 1 to 1000 1/sec. About 20% advancement in resiliency and 40% enhancement in dyeability were obtained. The dye uptake ability of fibers was also enhanced by adding NC to the blend. Moreover, the washing and light fastness, and staining on cotton and wool for all blend and blend nanocomposites were acceptable for textile fibers. The linear density of PP was enhanced slightly when 10 wt.% PTT was added. Further enhancements were observed by adding NC to the PP/PTT blend. However, PP shrinkage was decreased by incorporating PTT and NC.
Keywords: Blend; melt-spinning; nanoclay; poly(trimethylene terephthalate); polypropylene; yarn